2019
DOI: 10.1111/ocr.12331
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis for total mesialization of the mandibular dentition: A finite element study

Abstract: Objectives To clarify the mechanics of tooth movement in mesialization of the whole mandibular dentition when changing the force angulation. Setting A finite element method was used to simulate long‐term movements of the whole mandibular dentition. Material and methods Tooth movement was simulated by accumulating the initial displacement, which was produced by elastic deformation of the periodontal ligament. Mesial forces of 3 N were applied to the second molar bracket at −30°, −15°, 0°, 15° and 30° to the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Class II elastic is often used in treating patients with skeletal Class II malocclusion, which can cause rotation of the occlusal plane downward and backward. 16,18,21 There was a significant increase in the mandibular incisor inclination (L1-MP/°) and vertical position of mandibular first molars (L6-MP (mm)) before and after non-extraction treatment in this study. These results correlate with the findings of Janson et al 22 which have shown that there was a change in the mandibular incisor inclinations to the anterior and extrusion of the mandibular first molar.…”
Section: Discussionsupporting
confidence: 46%
“…Class II elastic is often used in treating patients with skeletal Class II malocclusion, which can cause rotation of the occlusal plane downward and backward. 16,18,21 There was a significant increase in the mandibular incisor inclination (L1-MP/°) and vertical position of mandibular first molars (L6-MP (mm)) before and after non-extraction treatment in this study. These results correlate with the findings of Janson et al 22 which have shown that there was a change in the mandibular incisor inclinations to the anterior and extrusion of the mandibular first molar.…”
Section: Discussionsupporting
confidence: 46%
“…Assuming the numerical data D = 2 mm, f r = 0.05 mm/rev, m 0 = 1.32 g given in 22 , the mass variation is . Based on the measured value of the elastic force in the tooth it is obtain that the order of nonlinearity is α = 1.03 23 and the rigidity coefficient is approximately k = 1 g/s 2 . Substituting the mass relation the equation of motion ( 7 ) is with initial conditions where is the initial deflection and is the initial velocity due to impact between the tooth surface and the drilling tool.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the numerical data D=2 mm, fr= 0.05 mm/rev, m0=1.32 g, v=15 m/min, the mass variation is = 1.32 − 0.002 . Based on the measured value of the elastic force in the tooth it is obtain that the order of nonlinearity is α=1.03 [22] and the rigidity coefficient is approximately k=1 g/s 2 . Substituting (35) the equation of motion ( 7) is Applying the Runge Kutta procedure the numerical solution of the equation (36) is computed.…”
Section: Discussionmentioning
confidence: 99%
“…32 − 0.002 )̈+ | | 0.03 = 0.002̇+ 0.02(22) with initial conditions (0) = 0 = 0.02 ,̇(0) = 0 = 0.5 , where 0 is the initial deflection and the function ( ) = 0.98557 −0.50372 .…”
mentioning
confidence: 99%